2007
DOI: 10.1103/physrevlett.99.157002
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Antiferromagnetism and Superconductivity in the Electron-Doped Cuprates Triggered by Oxygen Reduction

Abstract: We have performed a systematic angle-resolved photoemission study of as-grown and oxygenreduced Pr2−xCexCuO4 and Pr1−xLaCexCuO4 electron-doped cuprates. In contrast to the common belief, neither the band filling nor the band parameters are significantly affected by the oxygen reduction process. Instead, we show that the main electronic role of the reduction process is to remove an anisotropic leading edge gap around the Fermi surface. While the nodal leading edge gap is induced by long-range antiferomagnetic o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 24 publications
(26 reference statements)
3
26
2
Order By: Relevance
“…5 describes, this unusual Fermi surface is due to strong (π, π) antiferromagnetism, which gaps the quasiparticles near (π/2, π/2). Recent studies of the Re 2−x Ce x CuO 4 family have shown a clear link between oxygen content and the gapping of portions of the Fermi surface by antiferromagnetism [22][23][24] . Chemical and structural similarities between the two families strongly suggests that the energy pseudogap near (π/2, π/2) observed for Sr 0.90 La 0.10 CuO 2 may also be due to incomplete oxygen reduction.…”
Section: Doping Evolution Of Low-energy Statesmentioning
confidence: 99%
“…5 describes, this unusual Fermi surface is due to strong (π, π) antiferromagnetism, which gaps the quasiparticles near (π/2, π/2). Recent studies of the Re 2−x Ce x CuO 4 family have shown a clear link between oxygen content and the gapping of portions of the Fermi surface by antiferromagnetism [22][23][24] . Chemical and structural similarities between the two families strongly suggests that the energy pseudogap near (π/2, π/2) observed for Sr 0.90 La 0.10 CuO 2 may also be due to incomplete oxygen reduction.…”
Section: Doping Evolution Of Low-energy Statesmentioning
confidence: 99%
“…Effects of annealing are still not fully understood on the microscopic level: a small amount of oxygen atoms at the apical oxygen site1112, which stabilize the AFM ordering, and/or those at the regular site (in the CuO 2 plane or the LnO (Ln: rare earth) layer)13 are possibly removed by reduction annealing, while the discovery of secondary phase of Ln 2 O 3 created by annealing14 raised the possibility that annealing mends Cu defects existing in the as-grown sample by forming the Ln 2 O 3 phase1516. Previous ARPES studies have revealed that reduction annealing decreases the intensity of the AFM-folded bands and increase the spectral intensity at Fermi level ( E F )1718, but the AFM pseudogap has been seen in all the e-HTSCs from the underdoped to overdoped regions studied so far19. Therefore, the AFM pseudogap has been regarded as a hallmark of the e-HTSCs and the relationship between antiferromagnetism and superconductivity has been considered as a more essential ingredient of the e-HTSCs than the hole-doped ones.…”
mentioning
confidence: 99%
“…From the published ARPES data, reasonable values of the size and shape of the FS as well as the edge and corner Fermi velocities and scattering rates for excitation energies near the FS (below the observed kink in the energy dispersion) 17 are summarized in Table I for 10% and 12% doping levels. It should be noted that only one study reports the corner Fermi velocity where v c ∼ 0.4v e .…”
mentioning
confidence: 99%